Crime reporting behavior among Syrian immigrants in Istanbul - Özaşçılar, Mine (Crime & delinquency, 2019)
Research suggests that immigrants are reluctant to report crimes to the authorities. Turkey has recently witnessed a dramatic increase in the number of Syrian immigrants, who mostly reside in urban areas, particularly Istanbul and its surrounding cities. To rectify the complete lack of research on Syrians’ crime reporting, this study uses survey data collected from 380 Syrians in Zeytinburnu, Istanbul, to investigate Syrian immigrants’ willingness to report crime and the determinants of their crime reporting behavior. The findings suggest that Syrians are very willing to report crime to the police. In addition, satisfaction with the police and household size were positively correlated with crime reporting behavior.